Structural Influence on the Dominance of Virus-Specific CD4 T Cell Epitopes in Zika Virus Infection - Koblischke, Maximilian; Stiasny, Karin; Aberle, Stephan W.; Malafa, Stefan; Tsouchnikas, Georgios; Schwaiger, Julia; Kundi, Michael; Heinz, Franz X.; Aberle, Judith H. (Frontiers in Immunology, 2018)
Zika virus (ZIKV) has recently caused explosive outbreaks in Pacific islands, South- and Central America. Like with other flaviviruses, protective immunity is strongly dependent on potently neutralizing antibodies (Abs) directed against the viral envelope protein E. Such Ab formation is promoted by CD4 T cells through direct interaction with B cells that present epitopes derived from E or other structural proteins of the virus. Here, we examined the extent and epitope dominance of CD4 T cell responses to capsid (C) and envelope proteins in Zika patients. All patients developed ZIKV-specific CD4 T cell responses, with substantial contributions of C and E. In both proteins, immunodominant epitopes clustered at sites that are structurally conserved among flaviviruses but have highly variable sequences, suggesting a strong impact of protein structural features on immunodominant CD4 T cell responses. Our data are particularly relevant for designing flavivirus vaccines and their evaluation in T cell assays and provide insights into the importance of viral protein structure for epitope selection and antigenicity.